The ethics of carbon offsetting. (28th January 2013) - Hyams, Keith; Fawcett, Tina
Abstract: Carbon offsetting can be loosely characterized as a mechanism by which an organization or individual contributes to a scheme that is projected either to remove carbon dioxide from the atmosphere or to deliver carbon dioxide emission reductions on the part of other organizations or individuals. An activity that has been offset therefore purports to make no long‐term net contribution to atmospheric greenhouse gas concentrations. The ethical basis for using carbon offsetting as an approach to tackling climate change is very much contested. We seek to expose some of the underlying reasons for these ethical disagreements. We show that they relate both to empirical disagreements about what the likely benefits of offsetting are and, more fundamentally, to principled disagreements about the right way to discharge duties to deliver carbon reductions. WIREs Clim Change 2013, 4:91–98. doi: 10.1002/wcc.207 This article is categorized under: Climate, Nature, and Ethics > Ethics and Climate Change